Study on the Dynamic Simulation of Forest Landscape Pattern in Shangri-La Based on CLUE-S Model - Zhiwei Zhang, Zhiwei Yang, Keqin Xu, Li Sheng (Forest Chemicals Review)
The land utilization change date of three different stages (1999, 2009 and 2019) in Shangri-La was obtained by using the spatial-overlay approach for the space date. Furthermore, the CLUE-S model was applied to predict the trends in land use changes in the research area. On the base of land utilization space date in 2019, the factors of elevation height, gradient, exposure, roads and resident were considered in the CLUS-S model to imitate the land utilization spacial pattern change from 2019 to 2028. ROC method was used to verify the simulation results. The simulation of land using spatial pattern is based on the CLUE-S model, which can promote the management and sustainable development of protected areas and provide a scientific basis for forest landscape management and forest management.